2022
DOI: 10.1111/jgs.17737
|View full text |Cite
|
Sign up to set email alerts
|

Care preferences in physician orders for life sustaining treatment in California nursing homes

Abstract: Background Physician Orders for Life‐Sustaining Treatment (POLST) facilitates documentation and transition of patients' life‐sustaining treatment orders across care settings. Little is known about patient and facility factors related to care preferences within POLST across a large, diverse nursing home population. We describe the orders within POLST among all nursing home (NH) residents in California from 2011 to 2016. Methods California requires NHs to document in the Minimum Data Set whether residents comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…The completion of the POLST itself is not mandatory; documenting how it was completed is. In this issue of the Journal of the American Geriatrics Society , two articles by a team of researchers led by Jennings and Zingmond leverage the data produced by this mandate to examine how care preferences in NH patients are being documented in California and how that has changed over time 1,2 …”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…The completion of the POLST itself is not mandatory; documenting how it was completed is. In this issue of the Journal of the American Geriatrics Society , two articles by a team of researchers led by Jennings and Zingmond leverage the data produced by this mandate to examine how care preferences in NH patients are being documented in California and how that has changed over time 1,2 …”
Section: Figurementioning
confidence: 99%
“…In this issue of the Journal of the American Geriatrics Society, two articles by a team of researchers led by Jennings and Zingmond leverage the data produced by this mandate to examine how care preferences in NH patients are being documented in California and how that has changed over time. 1,2 Jennings et al reported three major findings. First, POLST completion rose in the 5 years following the mandate.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…11 But, fewer Black and Hispanic nursing home residents, compared to White residents, have POLST forms containing DNR orders. 12 Previous research concerning DNR orders in the inpatient setting suggests that racial and ethnic differences have not changed over time. 13,14 However, there is increasing interest in understanding variation in medical decision-making by race and ethnicity.…”
Section: Introductionmentioning
confidence: 99%
“…POLST—which requires formulation of resuscitation preference and other care preferences and ideally occurs before hospitalization—appears to be employed to about the same degree among White, Black, and Hispanic nursing home residents 11 . But, fewer Black and Hispanic nursing home residents, compared to White residents, have POLST forms containing DNR orders 12 . Previous research concerning DNR orders in the inpatient setting suggests that racial and ethnic differences have not changed over time 13,14 .…”
Section: Introductionmentioning
confidence: 99%